Juvenile granulosa cell tumor associated with Ollier disease - Sampagar, Abhilasha Ashok; Jahagirdar, Rahul R; Bafna, Vibha Sanjay; Bartakke, Sandip P (Indian Journal of Medical and Paediatric Oncology, 2016)
Juvenile granulosa cell tumor (JGCT) is a rare neoplasm of childhood. Interestingly, it is known to be associated with Ollier disease, which is a rare bone disease characterized by multiple enchondromatosis. There is paucity of literature about the co-occurence of these two conditions. However, this association is noteworthy because these two conditions share a common pathogenesis. We report a case of JGCT in a 2.5-year-old female child in which multiple enchondromas mimicking bony metastasis were an incidental finding during routine workup for tumor staging, thus leading to a diagnosis of Ollier disease.
Keywords: Enchondroma; juvenile granulosa cell tumor; Maffucci syndrome; Ollier disease